2019
DOI: 10.1016/j.jenvman.2018.10.113
|View full text |Cite
|
Sign up to set email alerts
|

Increased fire severity alters initial vegetation regeneration across Calluna-dominated ecosystems

Abstract: Calluna vulgaris-dominated habitats are valued for ecosystem services such as carbon storage and for their conservation importance. Climate and environmental change are altering their fire regimes. In particular, more frequent summer droughts will result in higher severity wildfires. This could alter the plant community composition of Calluna habitats and thereby influence ecosystem function. To study the effect of fire severity on community composition we used rain-out shelters to simulate drought prior to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 62 publications
0
48
2
Order By: Relevance
“…However, burning is also associated with warmer soils (Grau-Andrés et al, 2018a) that can lead to increased ER (Walker et al, 2018) and methane (CH 4 ) flux (Turetsky et al, 2014). In the longer term, post-fire changes in vegetation community composition (Grau-Andrés et al, 2019) may have the largest impact on soil C dynamics due to differences in C cycling between plant functional groups (Ward et al, 2009;Strack et al, 2017), including litter quality (Wardle et al, 2012) and transport mechanisms (e.g. aerenchymatous species can facilitate methane emission; Gray et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, burning is also associated with warmer soils (Grau-Andrés et al, 2018a) that can lead to increased ER (Walker et al, 2018) and methane (CH 4 ) flux (Turetsky et al, 2014). In the longer term, post-fire changes in vegetation community composition (Grau-Andrés et al, 2019) may have the largest impact on soil C dynamics due to differences in C cycling between plant functional groups (Ward et al, 2009;Strack et al, 2017), including litter quality (Wardle et al, 2012) and transport mechanisms (e.g. aerenchymatous species can facilitate methane emission; Gray et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…At the ditch scale, results are more variable and not consistent with those for pore waters ( Table 1). The studies we have identified (n=10) show a mean 10% increase in DOC concentrations following ditch blocking, although this figure is skewed by the large increases reported by Worrall et al (2007b) and Haapalehto et al (2014), and 170 the median change is 0. Importantly, no significant change in DOC concentration was reported in half of these studies (Armstrong et al, 2010;Evans et al, 2018;Gibson et al, 2009;O'Brien et al, 2008;Wilson et al, 2011).…”
Section: Ditch Blockingmentioning
confidence: 79%
“…There is little evidence to suggest that DOC concentrations or colour increase within pore water at the plot scale following managed burns. A recent study showed no change in DOC concentrations following low and high intensity burning (Grau-Andres et al, 2019), and in other cases plot scale DOC concentrations decreased (Clay et al, 2009;Worrall et al, 2007a). At the 320 catchment scale it has been suggested that managed burning contributed to increases in water colour and DOC concentrations Ramchunder et al, 2013), but these correlative studies were confounded by covariance between the extent of burning and peatland extent in the study catchments, and did not effectively take account of the concurrent effects of decreasing acid deposition (Chapman et al, 2008).…”
Section: Managed Burningmentioning
confidence: 82%
“…(purported 'peat-forming' plant species) to comparable unburnt or not recently burnt areas (e.g. Lee et al 2013a;Milligan et al 2018;Noble et al 2018a,b;Whitehead and Baines 2018;Grau-Andrés et al 2019a). Notably, the 'peat-forming' label is not supported by any robust experimental evidence (i.e.…”
Section: Peat-forming Species and Specific Indicators (Sphagnum Moss Species)mentioning
confidence: 99%